Winegrape similarities and concentrations: A description - German Puga; Kym Anderson (IVES Technical Reviews)
The aim of this article is to describe the mixes of winegrape varieties in the world’s main wine-producing countries. In doing so, we summarise a recent scientific journal article (Puga and Anderson 2023), in which we used data on area by variety for virtually all wine-producing countries and did some statistical analyses based on two indexes that we computed with those data. One of these indexes measures varietal similarities between countries, and the other measures varietal concentration within countries.